Comparing and analysing the content of Turkish and English local newspapers - Vural, Ali Murat (Loughborough University of Technology, 1991)
This dissertation begins by describing the importance, functions and circumstances of the local press and its influence on local people and their daily lives. Since one of the main aims of this research was to investigate the different characteristics of the local newspapers of the two countries (Turkey and England) and the particular local circumstances which affect each newspaper, it has been considered important to exa- mine the newspapers in various categories such as amount of news, number of advertisements, photographs, articles and features and the other information provided. Three Turkish and three English local newspapers have been cho- sen and studied over six months with 2-3 randomly chosen issues from each month. The results have been put into graphs and tables then commented upon. Finally the differences and similarities have been defined with their reasons and some observations and opinions have been suggested to Turkish local newspapers.
Sadece dijital ortamda erişilebilir.
Keywords: Yerel basın; Türk gazeteleri; İngiliz gazeteleri